Recent Progresses in Cancer Nanotherapeutics Design Using Artemisinins as Free Radical Precursors - Wu, Yalan; Zeng, Qingping; Qi, Zhiwen; Deng, Tao; Liu, Fang (Frontiers in Chemistry, 2020)
Artemisinin and its derivatives (ARTs) are sort of important antimalarials, which exhibit a wide range of biological activities including anticancer effect. To solve the issues regarding poor solubility and limited bioavailability of ARTs, nanoformulation of ARTs has thus emerged as a promising strategy for cancer treatment. A common consideration on nanoARTs design lies on ARTs’ delivery and controlled release, where ARTs are commonly regarded as hydrophobic drugs. Based on the mechanism that ARTs’ activation relies on ferrous ions (Fe2+) or Fe2+-bonded complexes, new designs to enhance ARTs’ activation have thus attracted great interests for advanced cancer nanotherapy. Among these developments, the design of a nanoparticle that can accelerate ARTs’ activation has become the major consideration, where ARTs have been regarded as radical precursors. This review mainly focused on the most recent developments of ARTs nanotherapeutics on the basis of advanced drug activation. The basic principles in those designs will be summarized, and a few excellent cases will be also discussed in details.